Analisis Zat Gizi Dan Karakteristik Sensoris Pukis Substitusi Tepung Mocaf Dengan Penambahan Tepung Daun Kelor - Fitriyanti, Addina Rizky; Pratiwi, Afinda; Sunarto, Sunarto; Luqyana, Novia Salma (Politeknik Negeri Jember, 2025)
Pukis cake is a traditional cake from Indonesia which is semi-circular in shape with yellow on the top and brown on the bottom. In general, pukis cakes are made from wheat flour, eggs, granulated sugar, margarine, yeast and coconut milk. Wheat flour as a raw material for making pukis serves as a structure builder and binds the other ingredients. As local food products develop, they can be substituted using mocaf flour and Moringa leaf flour. This research aims to determine the effect of substituting mocaf flour with the addition of moringa leaf flour on the nutritional value and sensory characteristics of pukis cakes. This research was purely experimental with a Completely Randomized Design (CRD) with 4 treatments and 6 repetitions. The percentage treatment of wheat flour, mocaf flour, and Moringa leaf flour is between P0 (250:0:12.5), P1 (187.5:62.5:12.5), P2 (125:125:25), and P3 (62.5:187.5:37.5). The results showed that the highest sugar content was in P3 (10.3%), fat content in P1 (13%), protein content in P1 (26.5), crude fiber content in P3 (18.4%), and water content. at P2 (28.6%). P1 substitution can increase the proportion of glucose, fat, protein and crude fiber; but reduce the proportion of water. P2 substitution can increase the proportion of glucose, crude fiber, and water; but reduces the proportion of fat and protein. P3 substitution can increase the proportion of glucose, crude fiber, and water; but reduces the proportion of fat and protein. The substitution of mocaf flour and Moringa leaf flour reduced the sensory color, taste, texture and aroma on pukis cake.